Sleep disturbance associations with blood pressure and body mass index in school-aged children - Restu Maharany Arumningtyas; Agung Triono; Retno Sutomo (Indonesian Pediatric Society, 2020)
Background Sleep disturbances can lead to many health problems in school-aged children, including hypertension and obesity. However, a lack of consensus about the etiology of these conditions is due to conflicting reports on the possible effects of sleep disturbances. Objective To assess for possible associations between sleep disturbances and blood pressure as well as body mass index in school-aged children. Methods This cross-sectional study involved primary school children in the 4th-5th grades. Subjects’ blood pressure, body weight, and body height were measured and their parents completed the Sleep Disturbances Scale for Children (SDSC) questionnaire. Results Of the 816 children enrolled, 503 (61.6%) children had sleep disturbances. The most common type of sleep disturbance was initiating and maintaining sleep. Bivariate analysis revealed a significantly increased risk of hypertension among subjects with sleep disturbances (PR 15.06; 95%CI 8.13 to 27.90) and increased risk of obesity (PR 22.65; 95%CI 12.28 to 41.78). Conclusion The most common type of sleep disturbance is initiating and maintaining sleep. Sleep disturbances are significantly associated with hypertension and obesity in children.